Molecular regulation of an invasion-related molecule: options for tumour staging and clinical strategies : position paper - Allgayer, Heike (European journal of cancer, 2006)
This review provides a summary of the European Association for Cancer Research Award Lecture, presented at the ECCO13 meeting in Paris in November 2005. It is a brief overview on the biological and clinical relevance of the urokinase receptor (u-PAR), an essential molecule to promote invasive and metastatic tumour phenotype and shown to be associated with early relapse and poor prognosis in many different types of cancers. The review summarizes the most important transcriptional mechanisms regulating u-PAR gene, and will focus on the differential binding of transcription factors to u-PAR promoter elements from studies in resected tumour and normal tissues of colorectal and gastric cancer patients. These studies conducted by our group may help to understand transcriptional mechanisms, which are employed to promote invasion and metastasis, in subpopulations of cancer patients. Such studies could lead to a more target-oriented patient selection and therapy against transcriptional and oncogeneic regulators in cancer.